2003
DOI: 10.1177/1077727x03031004005
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis between Recycled and Newly Manufactured Carpets

Abstract: Because of society's push to recycle plastics, to examine degradation properties of landfill items, and to use “green” materials in the interior design area, carpets must be investigated to these issues. This study examined the physical characteristics plus appearance retention factors associated with recycled nylon and polyester carpets as compared to newly manufactured carpets following testing using the Tetrapod Walker and soiling. Statistical design of project was completely randomized with a 2 × 2 × 3 (Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…For instance, some researchers investigated the thickness loss under dynamic and static loading [4][5][6][7] while others studied the carpet performance under short and long term static loading [8][9][10][11]. Additionally, in the literature there are many studies on mechanical, physical and appearance properties of carpet [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, some researchers investigated the thickness loss under dynamic and static loading [4][5][6][7] while others studied the carpet performance under short and long term static loading [8][9][10][11]. Additionally, in the literature there are many studies on mechanical, physical and appearance properties of carpet [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…At present, textiles in home furnishings are replaced more frequently due to changing styles instead of wearing out. This behavior contributes to increased waste streams and environmental problems (Watson & Warnock, 2003). Textile waste in the United States, including discarded clothing, furniture, carpets, and bed sheets, increased from 1.76 million tons to 16 million tons between 1960 and 2015 (U.S. Environmental Protection Agency, 2018).…”
mentioning
confidence: 99%
“…This accumulation of synthetic textiles in landfills as well as incineration of end-of-life textiles impacts water, soil, and air quality. The production of nylon, a widely manufactured synthetic fiber, has negative environmental impact at all levels: use of valuable petroleum resources, prolonged decomposition within a landfill, and harmful nitrous oxide emissions during production (Fletcher, 2014;Watson & Warnock, 2003;Rodie, 2010;Forum for the Future, 2007). In addition to the aforementioned impacts of synthetic fiber production, the increase in worldwide textile consumption has also created a steady decline in environmental status as valuable resources are being used daily that cannot be replaced.…”
Section: Environmental Concerns Of the Apparel And Textiles Industrymentioning
confidence: 99%
“…This restraint, combined with overfilling landfills and environmental decline, is forcing researchers and industry leaders to consider alternative resources such as recycling for textile production (Chen & Burns, 2006). Further market analysis revealed that companies are working on ways to separate the blended fibers for recycling and re-use, with great strides being made within the recycling of polyester fibers (Watson & Warnock, 2003). While many companies have begun using processes for recycling polyester, industry efforts regarding the recycling of nylon have lagged far behind (Chen & Burns, 2006).…”
Section: Recycling Processesmentioning
confidence: 99%
See 1 more Smart Citation